THU0435 Long-term outcome and prognosis factors of complications in thromboangiitis obliterans (BUERGER'S DISEASE): a multicenter study of 224 patients. (12th June 2018) - Le Joncour, A.; Soudet, S.; Dupont, A.; Espitia, O.; Koskas, F.; Cluzel, P.; Hatron, P.-Y.; Cacoub, P.; Resche-Rigon, M.; Lambert, M.; Saadoun, D.
Abstract : Background: Buerger's disease or thromboangiitis obliterans (TAO) is a non-atherosclerotic arteritis of distal extremities. Data regarding long term outcome of patients with Buerger's disease or thromboangiitis obliterans (TAO) are lacking and most series come from Middle-East and Far-East. Objectives: We aim report clinical presentation and assess long-term outcome and prognosis factors in a large cohort of TAO. Methods: Retrospective multicenter study of characteristics and outcomes of 224 TAO patients fulfilling Papa's and/or 5 Shinoya's criterias were analysed. Factors associated with vascular event free survival and amputation free survival were identified. Results: The median age at diagnosis was 38.5 32–46 years, 51 (28.5%) patients were female and 81.5% were Caucasians. All but 3 were smokers with a median of 22 pack-year and 22.8% were also addict to cannabis. At diagnosis, 53% had claudication, 73% trophic disorders and 8.8% an infection. Lower extremities and upper extremities were affected in 54% and 28% respectively. Superficial vein thrombosis, Raynaud's phenomen and arthralgia occurred in 18%, 41% and 8%, respectively. Ethnic group (non-Caucasian) and ischaemic ulcers or necrosis were independent factors of vascular events HR=7.67 [3.1–19.2] p=0.005 and 2.28 [1.3–4] p<0.001. At 15 years, amputation-free survival and major amputation-free survival were 66% and 91%, respectively. Infection was the only independent predictive factor of amputation HR=4.6[1.9–11], p<0001. Age, sex and cannabis addiction were not associated with events or amputation. Patient who stopped their tobacco consumption had lower vascular event (p=0.029) and amputation rate (p=0.001) than those who continued. Three patients died during follow-up. Conclusions: This nationwide study shows that 34% of TAO patients will experience an amputation within 15 years from diagnosis. We identified specific characteristics that identified those at highest risk for subsequent vascular complications. Disclosure of Interest: None declared